2019
DOI: 10.1177/0002764219850869
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Social Science Effect: An Intervention in Life Course Generosity

Abstract: Does interacting with social science data in early adulthood promote generosity? To investigate this question from a life course development perspective, two distinct samples were drawn for a survey with an embedded experimental design. The first sample is of emerging adult college students ( n = 30, median age = 20 years). The second sample is of young adults who were selected to participate based on their prior participation in a nationally representative and longitudinal study ( n = 170, median age = 31 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A field experiment carried out in a Swedish university demonstrated that descriptive social norms increased charitable giving of college students and the effect of local social norms of one's immediate environment is more powerful than that of global social norms (Agerström et al 2016). Another experimental study carried out in the United States also confirmed the effect of social norms on donation (Herzog et al 2019). Research on Chinese college students investigated and substantiated the effect of social norms on volunteering (Huang 2020;Luo et al 2012).…”
Section: Hypothesis 3b (H3b)mentioning
confidence: 97%
“…A field experiment carried out in a Swedish university demonstrated that descriptive social norms increased charitable giving of college students and the effect of local social norms of one's immediate environment is more powerful than that of global social norms (Agerström et al 2016). Another experimental study carried out in the United States also confirmed the effect of social norms on donation (Herzog et al 2019). Research on Chinese college students investigated and substantiated the effect of social norms on volunteering (Huang 2020;Luo et al 2012).…”
Section: Hypothesis 3b (H3b)mentioning
confidence: 97%